Determinants of productivity gap in the European Union: A multilevel perspective - Randolph Luca Bruno; Elodie Douarin; Julia Korosteleva; Slavo Radosevic (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
The paper explores the determinants of productivity gap within the European Union in four industrial manufacturing sectors (computers, chemicals, basic metals and food) of strong macroeconomic significance and varied "Research and Development" (R&D) intensity. Our analysis reveals that some of the most important factors determining productivity gap across the EU are related to technology gap variables - R&D intensity and R&D embedded in purchased equipment and machinery - and how they interact. While the signs for both R&D and embedded R&D are as expected and our results emphasise the relevance of technology for closing the productivity gap, this is not the case with the interaction between these two variables. The estimates for the interaction terms are indeed very significant and consistently negative in three out of four sectors. This negative relationship suggests that there is no complementarity between these two modes of technology acquisition - R&D and embedded R&D investments - which are however each separately crucial for catching up. In policy terms, this situation suggests that there is a lack of coordination between R&D policy and technology transfer (FDI, trade and industrial policy). Given that, our results also show a widening productivity gap between the countries of the EU periphery (South and East) and the rest of the sample.
Keywords: L60; O33; C55; 330; productivity; technology gap; multilevel analysis; European Union